1996
DOI: 10.1046/j.1365-2567.1996.d01-683.x
|View full text |Cite
|
Sign up to set email alerts
|

Limited heterogeneity of biased T‐cell receptor Vβ gene usage in lung but not blood T cells in active pulmonary sarcoidosis

Abstract: Sarcoidosis is a multisystem disorder characterized by non‐caseating granulomas and the accumulation of CD4+ T cells in involved tissues such as the lung. To evaluate the diversity of the CD4+ T‐cell repertoire in this disorder, a detailed clonal analysis was performed in five individuals with active sarcoidosis who demonstrated preferential accumulation of T cells expressing the T‐cell receptor variable gene family Vβ8 in either the lung or blood. In three individuals, analysis of unselected samples of nucleo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0
2

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 40 publications
(56 reference statements)
2
19
0
2
Order By: Relevance
“…These findings are consistent with an antigen-driven T-cell activation and the limited clonality of T-cells could also be demonstrated in sarcoid lung T-cells by analysing the nucleotide sequence of the TCR [156]. The association of this oligoclonality with the course of the disease is demonstrated by the fact that oligoclonality decreases after clinical improvement of the disease either by spontaneous remission or after corticoid therapy [156]. In addition, in some cases an amino acid motif in the V β /J β -region of the TCR could be identified which had not been described before and might therefore be typical for sarcoidosis [151].…”
Section: T-cellssupporting
confidence: 87%
See 2 more Smart Citations
“…These findings are consistent with an antigen-driven T-cell activation and the limited clonality of T-cells could also be demonstrated in sarcoid lung T-cells by analysing the nucleotide sequence of the TCR [156]. The association of this oligoclonality with the course of the disease is demonstrated by the fact that oligoclonality decreases after clinical improvement of the disease either by spontaneous remission or after corticoid therapy [156]. In addition, in some cases an amino acid motif in the V β /J β -region of the TCR could be identified which had not been described before and might therefore be typical for sarcoidosis [151].…”
Section: T-cellssupporting
confidence: 87%
“…However, KLEIN et al [89] demonstrated an increased percentage of V β 2, V β 3, V β 6 and V β 8 families in intradermal lesions of Kveim skin-tests compared with peripheral blood and that this increase was oligoclonal. These findings are consistent with an antigen-driven T-cell activation and the limited clonality of T-cells could also be demonstrated in sarcoid lung T-cells by analysing the nucleotide sequence of the TCR [156]. The association of this oligoclonality with the course of the disease is demonstrated by the fact that oligoclonality decreases after clinical improvement of the disease either by spontaneous remission or after corticoid therapy [156].…”
Section: T-cellssupporting
confidence: 77%
See 1 more Smart Citation
“…A cardinal feature of sarcoidosis is the presence of CD4+ T cells that interact with antigen-presenting cells to initiate the formation and maintenance of granulomas [75]. The oligoclonal αβ T-cell repertoire observed in sarcoidosis suggests that the triggering antigens favor progressive accumulation and activation of selective T-cell clones [76]. These activated CD4+ cells differentiate into type 1 helper T (Th1)-like cells and secrete predominantly interleukin-2 and interferon-γ, augment macrophage TNF-α production, and amplify the local cellular immune response [77].…”
Section: Immunopathogenesismentioning
confidence: 99%
“…These cells are activated and reduced numbers of cell surface TCR in the presence of increased TCR mRNA levels suggest downregulation of the TCR of pulmonary T cells in response to recent exposure to antigen [6]. Studies on the usage of TCR genes disclosed increased utilization of a restricted pattern of TCR Vα and Vβ gene products in the lung as compared with the blood in the majority of these patients, suggesting that the pulmonary T cell population is composed of an expanded oligoclonal component which superimposes itself on a polyclonal background [7, 8, 9, 10, 11, 12, 13, 14]. These clones are being further characterized to elucidate the nature of the putative antigens involved in the pathogenesis of sarcoidosis.…”
Section: Introductionmentioning
confidence: 99%